Come back, Africa [videorecording (DVD)] - Rogosin, Lionel, 1924-2000; Makeba, Miriam; Nkosi, Lewis; Modisane, Bloke, 1923-1986; Themba, Can, 1924-1968; Kirkpatrick, Frederick Douglass; Kennedy, Florynce, 1916-2000; Collier, Jim; Smith, Wendy; Johnson, Larry, 1938-; Davis, Gary, 1896-1972 (Milestone Film & Video, 2014)
In 1957, Rogosin travelled to South Africa and created a powerfully, moving drama exposing the harsh reality of life under the system apartheid. Filmed secretly under the noses of the feared South African police, Rogosin, his crew, and cast risked arrest and deportation. Miriam Makeba was banned from her country after travelling to Venice for the movie's premiere. The scenes shot in the vibrant black ghetto of Sophiatown are precious images of a lost world. Rogosin took the fight for equality to his homeland with Black roots, his documentary on African American life. The extraordinary cast, including Reverend Frederick Douglass Kirkpatrick, attorney and feminist activist Florynce "Flo" Kennedy, musicians Jim Collier, Wende [i.e. Wendy] Smith, Larry Johnson and Reverend Gary Davis, tell stories of heartbreak and despair while their songs blow the roof off the rafters. The film combines tales of oppression with hauntingly beautiful images of the faces of black men, women and children.